The Diagnostic Ability of Follow-Up Imaging Biomarkers after Treatment of Glioblastoma in the Temozolomide Era: Implications from Proton MR Spectroscopy and Apparent Diffusion Coefficient Mapping - Bulik, Martin; Kazda, Tomas; Slampa, Pavel; Jancalek, Radim (BioMed research international, 2015)
OBJECTIVE: To prospectively determine institutional cut-off values of apparent diffusion coefficients (ADCs) and concentration of tissue metabolites measured by MR spectroscopy (MRS) for early differentiation between glioblastoma (GBM) relapse and treatment-related changes after standard treatment. MATERIALS AND METHODS: Twenty-four GBM patients who received gross total resection and standard adjuvant therapy underwent MRI examination focusing on the enhancing region suspected of tumor recurrence. ADC maps, concentrations of N-acetylaspartate, choline, creatine, lipids, and lactate, and metabolite ratios were determined. Final diagnosis as determined by biopsy or follow-up imaging was correlated to the results of advanced MRI findings. RESULTS: Eighteen (75%) and 6 (25%) patients developed tumor recurrence and pseudoprogression, respectively. Mean time to radiographic progression from the end of chemoradiotherapy was 5.8 ± 5.6 months. Significant differences in ADC and MRS data were observed between those with progression and pseudoprogression. Recurrence was characterized by N-acetylaspartate ≤ 1.5 mM, choline/N-acetylaspartate ≥ 1.4 (sensitivity 100%, specificity 91.7%), N-acetylaspartate/creatine ≤ 0.7, and ADC ≤ 1300 × 10(-6) mm(2)/s (sensitivity 100%, specificity 100%). CONCLUSION: Institutional validation of cut-off values obtained from advanced MRI methods is warranted not only for diagnosis of GBM recurrence, but also as enrollment criteria in salvage clinical trials and for reporting of outcomes of initial treatment.
Keywords: nádory mozku; Sensitivity and Specificity; chemoradioterapie; senzitivita a specificita; Humans; lidé středního věku; Brain Neoplasms; hodnocení výsledků zdravotní péče; Biomarkers, Tumor; Female; výsledek terapie; lidé; glioblastom; dakarbazin; Outcome Assessment, Health Care; reprodukovatelnost výsledků; zobrazování difuzních tenzorů; nádorové biomarkery; Follow-Up Studies; ženské pohlaví; Dacarbazine; Diffusion Tensor Imaging; protonová magnetická rezonanční spektroskopie; Male; Middle Aged; Reproducibility of Results; prognóza; Treatment Outcome; Temozolomide; molekulární zobrazování; Glioblastoma; lokální recidiva nádoru; temozolomid; Proton Magnetic Resonance Spectroscopy; mužské pohlaví; Molecular Imaging; Neoplasm Recurrence, Local; Chemoradiotherapy; Prognosis; následné studie